A descriptive analysis of children seeking medical attention for problematic sexualized behavior - Thompson, Kara; Svendsen, Sasha (Frontiers in Psychiatry, 2023)
Introduction Problematic Sexualized Behavior (PSB) in children is an increasingly prevalent and often misunderstood issue that impacts the well-being of children. Quantifying the numbers of affected children is challenging due to inconsistencies in how these children are identified, as well as misperceptions surrounding the issue and lack of a coordinated community response. Methods In this single-center retrospective case review, we attempt to report data on child demographics and case characteristics for children presenting to one Child Protection Program (CPP) medical specialty team for concern of PSB. Results A total of 224 children were identified as having engaged in PSB during the study period. 110 (49%) of these children were referred to the CPP for medical evaluation and medically triaged by the team. The remaining 114 children (51%) were identified through the medical triage of the presenting cases as having engaged in PSB with the index children, but were not referred to CPP for medical care themselves. The majority of children who were referred (69%) were the recipient of the PSB, compared to being the displayer of the behavior (20%). Of the recipient cases, the child displaying PSB was also referred to the CPP only 14.5% of the time. Discussion These results highlight that the number of children presenting for medical evaluation with concern of PSB is a significant underestimation of the prevalence of PSB in the community. This notable gap in identification of children engaging in PSB prevents service delivery for these children, including medical evaluation. The results also demonstrate that children displaying PSB were disproportionately missing from care and represent a specific area of missed opportunity for intervention and support by medical professionals.